The Three Musketeers - Dumas, Alexandre; Translated by Lowell Bair (New York Bantam Classic, 2004)
During the reign of France's King Louis XIV, D'Artagnan and three musketeers unite to defend the honor of Anne of Austria against the plots of Cardinal Richeliu.
Keywords: France -- Swordsmen -- FICTION -- General